(untitled) (European Journal of Emerging Technology and Discoveries, 2023)
This article emphasizes the growing importance of educating students’ cognitive independence. Cognitive independence refers to the ability to think critically, solve problems, and engage in self-management. To develop these skills, teachers are increasingly turning to project-based learning (PBL) as an effective approach to learning. This article is aimed at studying the use of the project method for the development of cognitive independence in younger schoolchildren. It provides an overview of the methods used, presents the results and discusses the implications of this approach.